The size at reproduction of canopy tree species in central Africa - Ouédraogo, D-Y.; Doucet, J-L.; Daïnou, K.; Baya, F.; Biwolé, A.B.; Bourland, N.; Fétéké, F.; Gillet, J.F.; Kouadio, Y.L.; Fayolle, A. (Wiley, 2018)
Size at reproduction is a key aspect of species life history that is relatively understudied for long‐lived tropical trees. Here, we quantified reproductive diameter for 31 major timber species across 11 sites in Cameroon, Congo, and Central African Republic. Specifically, we examined whether (1) between‐species variability is correlated with other species traits; (2) reproductive diameter varies within‐species among sites; (3) reproductive status varies with crown exposure; and (4) the minimum cutting diameter limits (MCDL) imposed by national forest regulations enable seed trees to persist after logging operations. Consistent with studies conducted elsewhere in the tropics, we found great variability in diameter at reproduction among species, which correlated with adult stature (maximum diameter and height). For some species, reproductive diameter thresholds substantially varied between sites, and crown exposure had a significant positive effect on reproductive status. Most MCDLs were found to be suitable, with trees having a high probability of being seed trees at MCDL. Our findings have implications for the sustainable management of production forests, and they highlight questionable MCDLs for some species and between‐site variation in reproductive diameter. The study also highlights the need for long‐term phenological monitoring of tree species spanning a large range of ecological strategies to address both theoretical (species life history, allocation trade‐offs) and practical questions (MCDL).